2022
DOI: 10.1186/s43058-022-00275-5
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to improve the impact of two national clinical audit programmes: a theory-guided analysis

Abstract: Background Audit and feedback is widely used in healthcare improvement, with evidence of modest yet potentially important effects upon professional practice. There are approximately 60 national clinical audit programmes in the UK. These programmes often develop and adapt new ways of delivering feedback to optimise impacts on clinical practice. Two such programmes, the National Diabetes Audit (NDA) and the Trauma Audit Research Network (TARN), recently introduced changes to their delivery of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The findings were reported back to RACFs using evidencebased principles to trigger change. 12,14 Although it is anticipated that evidence-informed feedback can facilitate practice change, future research should explore the impact of the action plans. Given that staff working in RACFs are time poor, our feedback reports aimed to be brief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings were reported back to RACFs using evidencebased principles to trigger change. 12,14 Although it is anticipated that evidence-informed feedback can facilitate practice change, future research should explore the impact of the action plans. Given that staff working in RACFs are time poor, our feedback reports aimed to be brief.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the study findings was presented to participating facilities in the form of a short report (see File S3) and online presentation with discussion, using audit-and-feedback principles. [12][13][14] Specifically, we delivered the feedback in verbal and written (multimodal) formats, co-presented with a content expert, included explicit targets and an action plan, and the patient/resident voice was incorporated. IPC leads and managers were invited to attend the online discussion that was hosted by a researcher and an IPC expert from the IMMERSE team.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Chapter 4 A theory-guided evaluation of two national clinical audit programmes (objective 2) P arts of this chapter are reproduced or adapted with permission from Willis et al 97 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: https://creativecommons.org/licenses/by/4.0/.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of national audit programmes in the UK found that they often did not fully utilise existing evidence on effective feedback methods, for example incorporating action plans. 47,48 Audit and feedback has a long history in transfusion medicine. However, limited progress with repeated national audits in the UK motivated the AFFINITIE programme (Audit and Feedback INterventions to Increase evidence-based Transfusion practice).…”
Section: Au Dit a N D Fe E Dbackmentioning
confidence: 99%
“…However, there is still a gap between what audit and feedback can achieve and what is actually delivered. Analyses of national audit programmes in the UK found that they often did not fully utilise existing evidence on effective feedback methods, for example incorporating action plans 47,48 …”
Section: Audit and Feedbackmentioning
confidence: 99%